2020
DOI: 10.2147/dddt.s261283
|View full text |Cite
|
Sign up to set email alerts
|

<p>Bacterial Natural Compounds with Anti-Inflammatory and Immunomodulatory Properties (Mini Review)</p>

Abstract: Inflammation is part of the body’s complex biological response to harmful stimuli such as damaged cells, pathogens, or irritants. It is a protective response involving blood cells, immune cells, and molecular mediators. The inflammation not only can eliminate the primary cause of cell injury but also clears out necrotic cells, tissue damaged from the original insults and inflammatory process. Furthermore, it can initiate tissue repair. Pro-inflammatory cytokines are produced predominantly by activated macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…Proving these, in vitro pharmacological studies on the volatile oils (EOs) extracted from the aerial part of lavender species (Lavandula hybrid Rev., Lavandula latifolia Medikus., Lavandula vera D.C. and Lavandula angustifolia Miller cultivated in Bulgaria), MTS test on Caco-2 cells and Caco-2 cell morphology analysis by electron microscopy before and after the treatment with EOs, respectively, both experiments have been confirmed to have augmented cytotoxic effects of EOs on the colon cancer, and at the same time better effectiveness of EOs in comparison with the separate constituents (e.g., linalool and 1,8-cineole), explained by their synergistic and more selective effect [60]. There were also revealed antimicrobial and antioxidant effects of EOs from lavender species, which are very usefully in managing intestinal diseases in humans [60,61].…”
Section: Discussionmentioning
confidence: 81%
“…Proving these, in vitro pharmacological studies on the volatile oils (EOs) extracted from the aerial part of lavender species (Lavandula hybrid Rev., Lavandula latifolia Medikus., Lavandula vera D.C. and Lavandula angustifolia Miller cultivated in Bulgaria), MTS test on Caco-2 cells and Caco-2 cell morphology analysis by electron microscopy before and after the treatment with EOs, respectively, both experiments have been confirmed to have augmented cytotoxic effects of EOs on the colon cancer, and at the same time better effectiveness of EOs in comparison with the separate constituents (e.g., linalool and 1,8-cineole), explained by their synergistic and more selective effect [60]. There were also revealed antimicrobial and antioxidant effects of EOs from lavender species, which are very usefully in managing intestinal diseases in humans [60,61].…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, it is thought that exopolysaccharide's principal effect is to modulate cytokines and their related transcription factors [62]. TNF-α, IL-1, and IL-6, which are proinflammatory cytokines, and IL-10, which is an anti-inflammatory cytokine, are the primary mediators of these natural products' effects [63].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that various bene ts of probiotics to the host have been shown in numerous human clinical trials, the role of these organisms is to improve the balance of the intestinal ora and increase the production of short-chain fatty acids(SCFAs), which can directly or indirectly play the role of anti-in ammatory, protect the intestinal barrier function, regulate human metabolism and immunity [39][40][41]. Especially, (SCFAs) play an important role in the treatment of obesity, insulin resistance, diabetes and other metabolic diseases [42].As well as study showed that SCFAs can improve intestinal health by promoting the increase of intestinal barrier function and reducing the translocation of bacterial endotoxins on the intestinal wall, this is one of the reasons it reduces in ammation and improves insulin resistance [43].…”
Section: Discussionmentioning
confidence: 99%